2017
DOI: 10.1002/prs.11909
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Human Factors (HF) into a Process Safety Management System (PSMS)

Abstract: Human factors and process safety management (PSM) have become key factors in preventing exposure to both hazardous materials and major accidents. Therefore, comprehensive process safety management is required to address all aspects of human factors. Currently, there are several‐process safety management models all of which have some weaknesses with respect to the control of human factors inherent in the process industry. Moreover, there is as yet no universally accepted process safety management model that tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…The HFACS framework has been applied in retrospective incident analysis across numerous high-risk, high-reliability industries including aviation ( Li et al, 2008 , Li and Harris, 2013 , Wiegmann and Shappell, 2003 ; Zhou at al., 2018), maritime ( Chauvin et al, 2013 , Griggs, 2012 , Yıldırım et al, 2019 ), rail ( Baysari et al, 2008 , Madigan et al, 2016 , Reinach and Viale, 2006 ), mining ( Lenné et al, 2012 , Patterson and Shappell, 2010 ), oil and gas (Gholam Abbas et al, 2018; Theophilus et al, 2017 ), process safety management ( Theophilus et al, 2018 ), natural disaster management ( Brooks et al, 2018 ), and construction ( Sun et al, 2011 , Xia et al, 2018 , Ye et al, 2018 ). More recently, HFACS has been applied in the context of tertiary healthcare service delivery in hospitals ( Diller et al, 2014 ), surgery operating rooms ( Cohen et al, 2018a , Cohen et al, 2018b ; ElBardissi et al, 2007 , Thiels et al, 2015 ), pre-hospital emergency medical services ( Hughes et al, 2013 ), anaesthesiology incidents ( Neuhaus et al, 2018 ), trauma care ( Cohen et al, 2018a , Cohen et al, 2018b ), and in patient safety studies ( Hoffman et al, 2013 ).…”
Section: Human Factors Analysis and Classification System (Hfacs)mentioning
confidence: 99%
“…The HFACS framework has been applied in retrospective incident analysis across numerous high-risk, high-reliability industries including aviation ( Li et al, 2008 , Li and Harris, 2013 , Wiegmann and Shappell, 2003 ; Zhou at al., 2018), maritime ( Chauvin et al, 2013 , Griggs, 2012 , Yıldırım et al, 2019 ), rail ( Baysari et al, 2008 , Madigan et al, 2016 , Reinach and Viale, 2006 ), mining ( Lenné et al, 2012 , Patterson and Shappell, 2010 ), oil and gas (Gholam Abbas et al, 2018; Theophilus et al, 2017 ), process safety management ( Theophilus et al, 2018 ), natural disaster management ( Brooks et al, 2018 ), and construction ( Sun et al, 2011 , Xia et al, 2018 , Ye et al, 2018 ). More recently, HFACS has been applied in the context of tertiary healthcare service delivery in hospitals ( Diller et al, 2014 ), surgery operating rooms ( Cohen et al, 2018a , Cohen et al, 2018b ; ElBardissi et al, 2007 , Thiels et al, 2015 ), pre-hospital emergency medical services ( Hughes et al, 2013 ), anaesthesiology incidents ( Neuhaus et al, 2018 ), trauma care ( Cohen et al, 2018a , Cohen et al, 2018b ), and in patient safety studies ( Hoffman et al, 2013 ).…”
Section: Human Factors Analysis and Classification System (Hfacs)mentioning
confidence: 99%
“…[Zhang, 2012], (George and Renjith, 2022). An integrated process safety management system (IPSMS) model was established by Theophilus through incorporating Human Factors Analysis and Classification System (HFACS) framework into the process safety management (PSM) system [Theophilus, 2018]. In the IPSMS model, human factors were underlined.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] An abundance of process failure modes has caused many devastating chemical incidents, and in-depth explorations have shown that indirect causes of the consequences are human factors and weaknesses of management systems. 11 This was evident for the Macondo well blowout, as it was determined that the largest number of errors that led to the incident resulted from poor management and leadership. 12 A lack of safety training (TNG), incomplete risk management principles, failures to report unsafe conditions, and poor physical or mental states of workers affect human behavior, increase the likelihood of incidents.…”
Section: Introductionmentioning
confidence: 99%
“…However, analyses of these incidents concluded that management problems existed 8‐10 . An abundance of process failure modes has caused many devastating chemical incidents, and in‐depth explorations have shown that indirect causes of the consequences are human factors and weaknesses of management systems 11 . This was evident for the Macondo well blowout, as it was determined that the largest number of errors that led to the incident resulted from poor management and leadership 12 .…”
Section: Introductionmentioning
confidence: 99%